Women Muslim hardship after Al-Anbar Province War of Iraq - Novel Lyndon; Riyadh, A.J Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2020)
This article discusses the situation and experiences of women during a civil war between Sunni and Shiite Muslims in the region of Al Anbar, Iraq in 2013. The impact of the war had caused disruptions in terms of public order, properties and many people were killed. Although the women did not participate directly in the war, they suffered the consequences of the war. The present study was undertaken to investigate on how women attempted to cope with the situation during the war. The study was conducted based on qualitative approach using an in-depth interview method to obtain both primary and secondary data. A total of 25 informants were selected for the study. All informants had become widows as their husbands were killed during the war which resulted in destruction, murder, displacement, social circumstances and unstable political situations. The findings showed that the civil war had rendered women in Al-Anbar as widows. Women lost their honor, children and relatives as a result of immigration diseases in their attempts to escape the war. In conclusion, there was a need for the Sunni and Shiite Muslims to seriously consider the impact of war on women that required the Sunni and Shiite Muslims to put aside their respective ideological differences and to find a compromising and lasting peace in the province of Al-Anbar. In the final analysis, nobody accepts humiliation caused to women who suffered more than just killings, migration and random bombing